An experimental study on the performance of single slope solar still integrated with a PCM-based pin-finned heat sink. (January 2019) - Yousef, Mohamed S.; Hassan, Hamdy; Kodama, S.; Sekiguchi, H.
Abstract: The objective of this study is to improve the heat transfer characteristics of PCM storage unit, applicable to solar still system, using hollow cylindrical pin fins embedded in PCM. Hollow cylindrical pin fins act as thermal conductivity enhancer (TCE). In view of this, three cases are considered namely, Case 1: without PCM (conventional solar still), Case 2: solar still with PCM, Case 3: solar still with pin fins heat sink embedded in the PCM. The performance of the three cases is experimentally evaluated and compared to each other under the same climate conditions. The results revealed that the presence of PCM negatively affects the daytime freshwater productivity with a significant increment in the overall freshwater yield of the still. Also, solar still with PCM-based pin finned (Case 3) achieves the best thermal performance compared to conventional still (Case 1) and solar still with only PCM (Case 2). It is perceived that the total daily cumulative yield of distillate water of Case 3 is higher than those of case 1 and case 2 by 17 % and 7 %, respectively. Finally, the findings indicated that inclusion of PCM in the solar still systems for cases 2, 3 extends the production of fresh water after sunset by approximately 5h and 7h, respectively.